Copper recovery from chalcopyrite flotation plant tailings acid leach using ion exchange resin dowtm XUS 43578.00 - M. Mashingaidze, Melvin; N. Shifotoka, Catherine (International Journal of Engineering and Technology, 2018)
This study examined the feasibility of recovering copper from a sulphuric acid leach solution of chalcopyrite flotation plant tailings assaying 0.18 % copper and 0.19 % zinc using DOWTM XUS 43578.00 ion exchange resin. Zn2+cations are counter ionsto Cu2+cations during the ion exchange process. Adsorption and desorption tests were conducted on the resin with a leach solution containing26 mg Cu/L and 225 mg Zn/L,under various conditions of pH, DOWTM XUS 43578.00resin dosage, agitation time and eluant(ammonium hydroxide solution) concentration. The DOWTM XUS 43578.00resindemonstrated a high selectivity for copper over zinc, with a separation factor of 30.26 mg/g. The highcopper distribution coefficient of65L2/g2suggeststhe resin can effectively concentrate copper in leach solutions of these particular tailings.A 4M ammonium hydroxide solution yielded the highest copper recoveryat pH 3and0.6gresin dosageafter3hours of agitation. These results can be improved by a pre-treatment step to remove the zinc before the copper ion exchange process, and modifying the experiments to simulate industrial practice by having multi-stage sorption and desorption phases.Â